SOCIAL NETWORKING SITES AS A CHANNEL FOR DELIVERING INFORMATION ABOUT DURABLE PRODUCTS AND ITS IMPACT ON PURCHASING DECISIONS - Małgorzata Bartosik-Purgat (Acta Scientiarum Polonorum. Oeconomia, 2018)
The main objective of the paper is to identify the interdependencies between a type of a product (durable products) and the nature of information on social networking sites (SNSs) that affects the making of purchase decisions. An attempt has been made to answer the research question: to what extent types of products are of influence when using relevant information on SNSs and when making purchase decisions (pre-purchasing stage). The literary studies are complemented with empirical research done in three countries: China, Poland and the United States. The results confirm the importance of SNSs and the information obtained from them in making purchase decisions. In relation to the categories of products the strongest correlations were observed in fashion, household goods and cosmetics. In the case of the type of information gained through SNSs that influence making purchase decisions advertisements placed on SNSs and information about new products are the most significant.